Efektifitas Konseling Gizi pada Pasien Stroke Setelah Dipulangkan Terhadap Asupan Zat Gizi dan Aktifitas Fisik di RSUD dr. Doris Sylvanus Palangka Raya - Fretika Utami Dewi (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2019)
The occurrence of stroke is usually associated with the type of food consumed daily. Nutritional management is important, because it may prevent the recurrent of strokes. Therefore, a dietitian will provide nutrition counseling for patients before leaving the hospital. This study aimed to determine the outcomes of nutritional counseling in stroke patients after being discharged from RSUD dr. Doris Sylvanus Palangka Raya, especially in terms of their dietary intakes and physical activities. A cross sectional study design was employed involving as many as 30 patients in August and September 2018. Nutrient intake data were obtained from 3-day food record within 3 weeks while the Baecke questionnaire were used to assess patients’ physical activities. Data were analysed using ANOVA test. Results: Most of respondents were female, aged at 45 - 54 years, nonworking and basic education level. Providing a nutrition counseling before patients discharged from hospital positively affecting their physical activities (sig. 0.001), but not for dietary intakes (energy (sig. 0.394), fat (sig. 0.824), fiber (sig. 0.503), sodium (sig. 0,792), potassium (sig. 0,906), calcium (sig. 0,792)).